2013
DOI: 10.1039/c3mt20272k
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity in human multiple myeloma U266 cells: synergy between cryptotanshinone and arsenic trioxide

Abstract: Arsenic trioxide (As2O3) has been recently established as one of the most effective drugs for the treatment of patients with acute promyelocytic leukemia. However, it has exhibited to be less efficient for the non-promyelocytic leukaemia or other types of malignant tumors. The purpose of the present study was to explore new therapeutic strategies based on As2O3 for human multiple myeloma. Here, we first report cryptotanshinone (CPT) and As2O3 synergy for enhanced cytotoxicity in human multiple myeloma U266 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…Western blot analysis was performed as previously described. 34 Briefly, gastric cancer cells were washed in phosphate-buffered saline, lysed for 30 min using RAPI extraction buffer (Beyotime Institute of Biotechnology, Jiangsu, China) containing freshly prepared protease inhibitors (Merck, Germany) and then centrifuged for 5 min at 14,000 rpm at 4℃. The protein concentration of the supernatant was determined using the BCA protein assay (Pierce, Rockford, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as previously described. 34 Briefly, gastric cancer cells were washed in phosphate-buffered saline, lysed for 30 min using RAPI extraction buffer (Beyotime Institute of Biotechnology, Jiangsu, China) containing freshly prepared protease inhibitors (Merck, Germany) and then centrifuged for 5 min at 14,000 rpm at 4℃. The protein concentration of the supernatant was determined using the BCA protein assay (Pierce, Rockford, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondria from cultured cells were isolated as described previously (Liu et al, ). In brief, 2 × 10 7 cells were frozen and thawn to weaken the cell membrane, and then suspended in ice‐cold homogenization buffer A [230 mM Mannitol, 70 mM sucrose, 10 mM Tris‐HCl, is‐HCl 0% of homo sub‐1 mM EDTA·2Na and 0.5% bovine serum albumin (BSA), pH 7.4] and incubated for 10 min on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Jian et al showed that ATO upregulates cereblon, the antimyeloma target of LEN, thus potentiating the sensitivity of MM cells [98]. The anti-myeloma activity of ATO was also enhanced by the combination strategies with a vitamin E analog Trolox [99], a specific MEK inhibitor PD325901 [100], a natural quinoid diterpene cryptotanshinone (also known as STAT3 inhibitor) [101,102], and a phytochemical sulforaphane [103].…”
Section: Multiple Myeloma (Mm)mentioning
confidence: 99%